"Seeing Her Through a Bamboo Curtain": Envisaging a National Literature through Chinese Folk Songs. (1st September 2016) - Shao, Flora
Abstract : In 1922, Chang Hui (1894–1985) published in Folk Song Weekly ten ballads with a shared motif: "seeing her through a bamboo curtain" ( gezhe zhulian kanjian ta ). Regarding the ballads as at once ten place-based, local folk songs and one placeless, national poetry, Chang urged attention to the exemplary influence of folk songs on the unification of languages in early twentieth-century China. Throughout the folk song campaign (c. 1918–c. 1927), however, the potential of folk songs to facilitate nationalization of Chinese language and literature remained arguably unfulfilled. This article examines the reasons for folk songs' lack of influence on modern Chinese literary history. Through an analysis of contesting ideas and agendas regarding the literary nature of folk song, the author reveals that folk songs were rediscovered at a moment of modern Chinese history when prevalent discourses on Chinese language and literature could not fully accommodate the folk, the dialect, or the oral nature of folk song.